2016
DOI: 10.3324/haematol.2016.142752
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET as a biomarker for early response in diffuse large B-cell lymphoma as well as in Hodgkin lymphoma? Ready for implementation in clinical practice?

Abstract: A short historyMajor changes have taken place in the staging and response assessment of malignant lymphoma in the last two decades. With the introduction of fluorodeoxyglucose-positron emission tomography (FDG-PET) and positron emission tomography-computed tomography (PET-CT), the criteria for staging and monitoring response have changed dramatically. In the revised Cheson criteria published in 2007, 1 staging with FDG-PET was still optional, and end-of treatment assessment using FDG-PET and CT was obligatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The study reported that iPET scan assessed by deltaSUV but not Deauville score accurately predicted better 2‐year PFS (79.4% vs. 36.7%, p < .0001) and 2‐year OS (88.2%vs 59% p < .0001) in those patients with negative scans across all lymphoma types. However, escalation of treatment based on positive iPET did not translate into improved outcomes, similarly to several earlier trials, demonstrating the limitations of interim PET CT in guiding therapy in DLBCL 18 …”
Section: Risk Stratificationsupporting
confidence: 62%
“…The study reported that iPET scan assessed by deltaSUV but not Deauville score accurately predicted better 2‐year PFS (79.4% vs. 36.7%, p < .0001) and 2‐year OS (88.2%vs 59% p < .0001) in those patients with negative scans across all lymphoma types. However, escalation of treatment based on positive iPET did not translate into improved outcomes, similarly to several earlier trials, demonstrating the limitations of interim PET CT in guiding therapy in DLBCL 18 …”
Section: Risk Stratificationsupporting
confidence: 62%
“…A response-adapted design has failed to improve patient outcomes in several recent prospective trials in patients with aggressive NHL [ 94 ] with the exception of one study presented by the Australian Leukemia and Lymphoma Group [ 95 ]. This study enrolled 162 patients with poor prognosis DLBCL.…”
Section: Response-adapted Treatment Using Fdg Petmentioning
confidence: 99%
“…Application of 18 F-FDG PET during therapy (interim-PET, or I-PET) allows PET-guided patient management, with success in Hodgkin lymphoma (5)(6)(7)(8). In DLBCL, the value of I-PET is less clear (9): most I-PET-adapted trials in DLBCL did not demonstrate a strategy that overcomes treatment resistance (10), except for a phase II study with intensification after rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) at a 14-d cycle (R-CHOP14) in I-PET-positive patients to R-ICE and Z-BEAM autologous stem cell transplantation (11). Therefore, I-PET is currently not used in clinical practice.…”
mentioning
confidence: 99%